Design, synthesis, biological evaluation, QSAR analysis and molecular modelling of new thiazol-benzimidazoles as EGFR inhibitors. Issue 18 (15th September 2020) - Srour, Aladdin M.; Ahmed, Nesreen S.; Abd El-Karim, Somaia S.; Anwar, Manal M.; El-Hallouty, Salwa M.
Graphical abstract: New functionalized thiazol-benzimidazole derivatives were designed, synthesized and evaluated for their in vitro EGFR inhibiting activities. In vitro anti-breast cancer activity of the promising derivatives was also evaluated. The pro-apoptotic activity of the analogue 4a was evaluated against caspase-3, p53, Bax/Bcl-2 expression levels, cell cycle analysis as well as PARP-1 inhibition. QSAR analysis and molecular modelling studies were carried out representing the binding modes of the promising compounds in the active pocket of EGFR. Highlights: New thiazol-benzimidazole derivatives 4a-q have been synthesized. Utilizing EGFR as a putative target, the new compounds 4a-q were evaluated in vitro as EGFR inhibitors. The promising compounds (4a, 4b, 4d, 4f, 4h, 4i, 4j, 4m, 4n ) were examined as anticancer agents against MCF-7 cancer cells. Compound 4a was selected to study its effect on cell cycle and apoptosis induction as well as its pro-apoptotic activity against caspase-3, p53, Bax/Bcl-2 and PARP-1 expression levels. QSAR and molecular modelling of 4a, 4d, 4h, 4i and 4n were also performed to elucidate their binding modes with amino acid residues of EGFR. Abstract: Heterocyclic rings such as thiazole and benzimidazole are considered as privileged structures, since they constitute several FDA-approved drugs for cancer treatment. In this work, a new set of 2-(2-(substituted) hydrazinyl)-4-(1-methyl-1 H -benzo[ d ]imidazol-2-yl) thiazoles 4a-q were designed as epidermal growth factor receptor (EGFR) inhibitors and synthesized using concise synthetic methods. The new target compounds have been evaluated in vitro for their suppression activity against EGFR TK. Compounds 4n, 4h, 4i, 4a and 4d exhibited significant potency in comparison with erlotinib which served as a reference drug (IC50, 71.67–152.59 nM; IC50 erlotinib, 152.59 nM). Furthermore, MTT assay revealed that compounds 4j, 4a, 4f, 4h, 4n produced the most promising cytotoxic potency against the human breast cancer cell line (MCF-7) (IC50; 5.96–11.91 µM; IC50 erlotinib; 4.15 µM). Compound 4a showed promising activity as EGFR TK inhibitor as well as anti-breast cancer agent. In addition, 4a induced apoptotic effect and cell cycle arrest at G2/M phase preventing the mitotic cycle in MCF-7 cells. Moreover, 4a upregulated the oncogenic parameters; caspase-3, p53, Bax/Bcl-2 as well as it inhibited the level of PARP-1 enzyme. QSAR study was carried out for the new derivatives and it revealed the goodness of the models. Furthermore, molecular docking studies represented the binding modes of the promising compounds in the active pocket of EGFR.